Analysis of disease activity categories in chronic spontaneous/idiopathic urticaria. (1st October 2017) - Stull, D.; McBride, D.; Tian, H.; Gimenez Arnau, A.; Maurer, M.; Marsland, A.; Balp, M.‐M.; Khalil, S.; Grattan, C.
Summary: Background: Measurement of disease activity guides treatment of chronic spontaneous urticaria (CSU). A weekly Urticaria Activity Score – here, the average of twice‐daily patient assessment of itch and hives scores summed over 1 week (UAS7TD ) – measures severity from 0 to 42. Insufficient evidence exists on whether disease activity states, defined by categorical UAS7TD scores, correlate with other patient‐reported outcomes and treatment response. Objectives: To evaluate and compare categorical UAS7TD scores with selected measures of disease‐related quality of life and impact. Methods: Data from three randomized clinical trials of omalizumab in CSU were pooled. Continuous UAS7TD scores were categorized into five disease activity states: urticaria‐free, well‐controlled, mild, moderate and severe urticaria. Total scores from the Dermatology Life Quality Index; the Chronic Urticaria Quality of Life questionnaire; and questions on sleep and daily activity interference, presence of angioedema and diphenhydramine use were compared within categorized UAS7TD disease‐state scores, using anova for analysis at different time points and mixed‐effects regressions for analysis of all data pooled. Results: Pooled analyses showed that categorical UAS7TD disease states accurately predicted differences among treated patients with CSU with different levels of disease activity. A consistent pattern existed between categories, with higher‐activity disease states associated with significantly higher impact and an increase in angioedema frequency. Results at different treatment time points were consistent. Conclusions: Categorical UAS7TD disease states can discriminate between measures when considering the impact of urticaria activity. Using five categorical disease states could simplify clinical assessment and monitoring of treatment efficacy.